2020
DOI: 10.3390/cancers12030700
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Deregulated Pathways, Key Regulators, and Novel miRNA-mRNA Interactions in HPV-Mediated Transformation

Abstract: Next to a persistent infection with high-risk human papillomavirus (HPV), molecular changes are required for the development of cervical cancer. To identify which molecular alterations drive carcinogenesis, we performed a comprehensive and longitudinal molecular characterization of HPV-transformed keratinocyte cell lines. Comparative genomic hybridization, mRNA, and miRNA expression analysis of four HPV-containing keratinocyte cell lines at eight different time points was performed. Data was analyzed using uns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 58 publications
1
29
1
3
Order By: Relevance
“…Recently attention has been directed at the contribution of microRNAs (miRs) to the HPV life-cycle and HPV-induced carcinogenesis. A wide range of miRs have been found to have altered expression in the presence of HPV E6/E7, affecting a wide range of centrally important cellular signalling pathways [ 159 , 160 ], including those involved in control of cell growth [ [161] , [162] , [163] , [164] ] and apoptosis [ 165 , 166 ].…”
Section: Epigenetic Regulation and Micrornasmentioning
confidence: 99%
“…Recently attention has been directed at the contribution of microRNAs (miRs) to the HPV life-cycle and HPV-induced carcinogenesis. A wide range of miRs have been found to have altered expression in the presence of HPV E6/E7, affecting a wide range of centrally important cellular signalling pathways [ 159 , 160 ], including those involved in control of cell growth [ [161] , [162] , [163] , [164] ] and apoptosis [ 165 , 166 ].…”
Section: Epigenetic Regulation and Micrornasmentioning
confidence: 99%
“…While the mRNA levels of ATG13 and ULK1 encoding key factors in the autophagy pathway were also upregulated, though the activity of their protein products is negatively regulated by mTORC1 [29], revealing other factors may exist to regulate autophagy besides mTOR. Recently, a relevant study by Babion et al indicated that mTOR signaling was one of the three altered pathways in HPV-induced carcinogenesis, in which dysregulation was induced by the copy number changes of respective genes [30]. This provides a novel strategy to study the dysregulated expression of key genes in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic accuracy for each candidate transcript was assessed individually by constructing receiver operating characteristic (ROC) curves and calculating the area under the curve (AUC), using an independent cohort, GSE138080 (65). The cohort was chosen due to the balanced number of subjects in the respective groups.…”
Section: Diagnostic Accuracy and Tumor Infiltration Analysismentioning
confidence: 99%